Pengolahan Air Gambut Menggunakan Magnetit dan Filtrasi Dengan Pasir Kerang - Asbanu, Govira Christiadora; Kadaria, Ulli (Al-Ard: Jurnal Teknik Lingkungan, 2024)
Peat soil is composed mainly of organic matter, which directly impacts on the water quality in peatlands. The water in peatlands, also known as peat water, is high in organic matter, low in pH, and brown in colour. To make it suitable for daily use, such as bathing and toilet flushing, peat water must be treated. This research aims to treat peat water using Fe3O4 to reduce organic matter and a filtration process with shell sand to overcome pH and turbidity issues. The research results showed that the maximum dose of Fe3O4 to reduce turbidity is 0.0002 g/mL. Higher doses of Fe3O4 were found to increase turbidity due to the dissolution of Fe in peat water. The filtration process of peat water treated with Fe3O4 in improved pH levels that meet the quality standards. However, it also increased the turbidity due to the dissolution of fine shell sand particles in the peat water. To obtain the best conditions for effective adsorption of particles that cause turbidity, pH conditioning must be carried out before adding Fe3O4. It is also necessary to standardize the particle size of shell sand to minimize the dissolution of fine particles that can increase turbidity.